2019
DOI: 10.1021/acs.jmedchem.9b01697
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Based Allosteric Inhibitors of Zika and Dengue Virus NS2B/NS3 Proteases

Abstract: The NS2B/NS3 serine proteases of the Zika and Dengue flaviviruses are attractive targets for the development of antiviral drugs. We report the synthesis and evaluation of a new, proline-based compound class that displays allosteric inhibition of both proteases. The structural features relevant for protease binding and inhibition were determined to establish them as new lead compounds for flaviviral inhibitors. Based on our structure–activity relationship studies, the molecules were further optimized, leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 71 publications
5
90
0
Order By: Relevance
“…Using computational approaches, the localization of probable allosteric sites in ZIKV NS2B/NS3 pro and CHIKV nsP2 pro were defined previously [46,69,70]. They described that The residues involved in the interaction between protease and HST are labeled.…”
Section: Plos Onementioning
confidence: 99%
“…Using computational approaches, the localization of probable allosteric sites in ZIKV NS2B/NS3 pro and CHIKV nsP2 pro were defined previously [46,69,70]. They described that The residues involved in the interaction between protease and HST are labeled.…”
Section: Plos Onementioning
confidence: 99%
“…The highest inhibition of cathepsin L was found with the benzoic acid amide 4 (K i = 0.66 µM) and the amine 7 (K i = 1.6 µM). The latter also turned out to be the best inhibitor of cathepsin B and the Dengue virus (DENV) protease [47,48], however with lower inhibitory potency (Cath. B: K i = 4.4 µM; DENV PR: 31% at 20 µM).…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…In general, an adaptation of methods described by Tanja and collaborators (2019) was used [ 79 ]. Initially, aniline (1.0 eq.)…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, 1 H NMR analysis showed that the chemical shifts (δ) for the hydroxyl (OH) from the carboxylic acid can appear between 12.38 and 12.71 ppm. Subsequently, the acrylamide derivatives (LQM328-337) were obtained by the TBTU-coupling reaction (Figure 3), using diisopropylethylamine (DIPEA) as a catalyst base [79], with yields from 52 to 92%. For all these final compounds, the purity degree was determined by the HPLC technique, which resulted in purities ranging from 95.3 to 99.9%, with retention time (R T ) between 3.07 and 3.88 min.…”
Section: Chemistrymentioning
confidence: 99%